Survey of Power System Restoration Documents Issued from 2016 to 2021 - H. Khoshkhoo; M. Khalilifar; S. M. Shahrtash (International Transactions on Electrical Energy Systems)
More than thirty-six partial or whole blackouts, from 2016 to 2021, prove that neither the probability of blackouts can be ignored nor the required plans and the readiness of the utilities for power system restoration can be forgotten. To properly deal with blackouts and minimize the social and economic costs, utilities should prepare a suitable restoration plan in advance to quickly restore the system to the normal state and minimize the restoration time and loss of energy. In this paper, after summarizing major blackouts occurred from 2016 to 2021, the progress in the research reports, industrial documents, and books in the context of power system restoration is reviewed to show and classify the different aspects of power system restoration plans and strategies presented during these years. This review indicates that although there are many published methods and techniques which have tried to give more autonomous solutions, there are still more complexities in power system restoration. However, this paper respects all efforts and attempts and tries to illustrate the achievements, up to now, in power system restoration, as well as research gaps.